Optimization of process parameter in drilling of snake grass fiber reinforced composites. (2022) - Saravanakumar, A.; Aravindanath Reddy, S.
Abstract: Natural fiber composites are at present more appropriate replacement for synthetic fibers such as carbon, glass and Kevlar fibers in several applications. In the current investigation an attempt is made to fabricate and examine the thrust force and surface roughness of Snake Grass Fibers reinforced composite. Composites were manufactured with Snake Grass Fiber as reinforcement along with epoxy resin as matrix using hand lay-up method. With the sample natural fiber reinforced composites drilling test has been conducted to learn the factor effect on the Thrust force of drilled unidirectional Snake Grass Fibers reinforced composites (SGFRC). L9-Taguchi method was used to perform the drilling experiments. Thrust force estimated with different factors like spindle speed, feed and drill diameter considered for this investigation with the help of smaller the better concept of Taguchi method as objective function. Further regression equation utilized to find Thrust force that with best possible combination with better result compared to experimental values. From the results, it was found that optimum value of thrust force was obtained at 1800 rpm spindle speed, 10 mm/min of feed and 4 mm drill diameter.